PARENT INVOLVEMENT IN EARLY CHILDREN'S LEARNING GUIDANCE DURING PANDEMIC - Umi Hani; Ichsan Ichsan; Nailul Falah (UIN Sunan Kalijaga Yogyakarta, 2021)
AbstractGuiding learning in early childhood during a pandemic is very different from adults because children are not yet independent and still need parental assistance and guidance. Parental involvement is a key part of the success of a child's learning process. This study aims to determine the level of achievement of parental involvement in learning guidance children during the pandemic. The research method used is descriptive quantitative with descriptive statistical analysis and data collection using interviews, documentation and questionnaires on parental involvement in early childhood learning guidance. The population of this study were parents of Darussalam Plus Kindergarten students totaling 94 people. The results showed that. Parental involvement in child learning guidance is good as evidenced by parental involvement in the provision of facilities and infrastructure 74%, supervision of learning at home 70%, communicating with schools 67%, encouraging the study of religious knowledge 68% and quite good in providing motivation as much as 46%. Factors supporting success include the availability of preventive and curative efforts from schools. Keywords: Parental involvement, learning guidance, pandemic AbstrakMembimbing belajar pada anak usia dini pada masa pandemi sangatlah berbeda dengan orang dewasa, karena anak anak belum mandiri dan masih membutuhkan pendampingan dan bimbingan orang tua. Keterlibatan orang tua menjadi bagian kunci sukses keberhasilan proses belajar anak. Penelitian ini bertujuan untuk mengetahui tingkat pencapaian keterlibatan orang tua dalam bimbingan belajar anak pada masa pandemi. Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan analisis statistik deskriptif dan pengumpulan data menggunakan wawancara, dokumentasi dan angket keterlibatan orang tua dalam bimbingan belajar anak usia dini. Populasi penelitian ini adalah orang tua murid TK Darussalam Plus berjumlah 94 orang. Hasil penelitian menunjukkan bahwa. keterlibatan orang tua dalam bimbingan belajar anak adalah baik dibuktikan dengan partisipasi keterlibatan orang tua dalam penyediaan sarana dan prasarana 74 %, pengawasan pembelajaran di rumah 70%, melakukan komunikasi dengan sekolah 67 % , mendorong belajar ilmu agama 68% dan cukup baik dalam pemberian motivasi sebanyak 46 %. Faktor pendukung keberhasilan antara lain tersedia upaya preventif dan kuratif dari sekolah. Kata kunci: Keterlibatan orang tua, bimbingan belajar, pandemi